Federalism and Constitutional Law The Italian Contribution to Comparative Regionalism - ARBAN, ERIKA; Martinico, Giuseppe; PALERMO, Francesco (Taylor & Francis, 2021)
"This volume examines the relationship between central government and local institutions, taking Italy as a case study to present a comparative perspective on how the Italian experience has influenced the global developments of federal and regional states. As the country with the longest standing regional system, Italy has a lot to tell countries that are dealing with similar issues in present times. Adopting a theoretical/analytical approach coupled with comparative analysis, this volume critically reflects on the changes brought to the Italian system of government by the reform of Title V of the Italian constitution, the reasons why further decentralisation has been resisted and offers a comparative overview of the place and contributions that the Italian experience has brought to the global debate on regionalism and federalism. The book is divided into two parts: Part I distils the essence of the evolution of Italian regionalism and the respective debate before and after 2001. While focusing on Italy, the various chapters situate it within the global framework of discussion. Part II reflects on how the Italian regional constitutional architecture contributes to the global debate, particularly focusing on the main innovations brought about by constitutional reform. The book will be essential reading for researchers, academics and policy-makers working in the areas of constitutional law and politics, and federalism."